Electrochemically induced amorphous and porous VOx/N-doped carbon spheres as a cathode for advanced aqueous zinc-ion batteries. Issue 3 (21st December 2022) - Yuan, Jujun; Gan, Yunfei; Mou, jirong; Ma, Xiangdong; Li, Xiaokang; Meng, Junxia; Xu, Lishuang; Zhang, Xianke; He, Haishan; Liu, Jun
Abstract : Vanadium-based oxides have captured considerable attention as ZIB cathodes benefiting from their rich valences and superior theoretical capacity. Abstract : Vanadium-based oxides have captured considerable attention as ZIB cathodes benefiting from their rich valences and superior theoretical capacity. However, vanadium-based oxides still suffer from structural instability, low electronic conductivity, and slow reaction dynamics, which will lead to poor zinc ion storage performance. Herein, amorphous VO x /NC porous spheres were fabricated by in situ, electrochemically-induced vanadium-polydopamine-derived crystalline V2 O3 /NC porous spheres. As a zinc-ion battery cathode, the VO x /NC porous spheres exhibit a sustainable capacity of 233 mA h g −1 at 5 A g −1 upon 1500 cycles and superior rate property. The excellent electrochemical performance of the VO x /NC porous-sphere electrode is ascribed to its distinctive architecture. The VO x /NC porous spheres possess amorphous VO x with a higher oxidation states of V 5+ /V 4+, which can increase the theoretical energy density, provide more active sites, and improve Zn 2+ diffusion kinetics. Furthermore, VO x /NC porous spheres with a porous core–shell architecture can enhance electrical conductivity and ensure electrolyte accessibility. This synthesis strategy can be potentially extended to fabricate other VO x /carbon composites with high valence states (V 5+ and V 4+ ).